Effect of compressor-discharge-cooler heat-exchanger length using condensate water on the performance of a split-type air conditioner using R32 as working fluid - Setyawan, Andriyanto; Sumeru, Kasni; Pramudantoro, Triaji Pangripto; Muliawan, Rizki; Tohir, Toto; Sukri, Mohamad Firdaus (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The utilization of condensate water as a compressor-discharge cooler results in subcooling on the condenser outlet. On the other hand, a split-type air conditioner (A/C) with R32 as working fluid can provide higher compressor-discharge temperatures than other refrigerants used in the same A/C. Therefore, A/C working with R32, equipped with a heat exchanger by utilizing waste-condensate water as the compressor-discharge cooler, has promising potential to produce the largest subcooling effect in air-conditioning systems. The aim of this study is to investigate the effect of condensate water as the compressor-discharge cooler on the performance of an A/C using R32 as the working fluid with different sizes of heat exchanger. The experimental study was carried out on the A/C with a compressor capacity of 1.1 kW, using three different heat-exchanger lengths, i.e., 18, 20 and 22 cm. The results indicated that longer heat exchangers produced higher degrees of sub-cooling; the heat exchangers with lengths of 18, 20 and 22 cm produced average degrees of subcooling of 0.9, 1.5 and 4.5 K, respectively. Therefore, increments in the degree of subcooling generate improvements in cooling capacity, lowering the compressor-input power, and enhance the COP of the A/C. The average COP improvement of the A/C with heat-exchanger lengths of 18, 20 and 22 cm were 9.1, 14.4 and 27.3%, respectively.